IMPROVING BUSINESS QUALITY THROUGH MANAGEMENT TRAINING AND MARKETING STRATEGIES - Siti Mariam; Irwan Sugiarto; Retno Wulansari; Eko Cahyo Mayndarto; Rudi Ginting; Noryani Noryani (Yayasan Education and Social Center, 2022)
Competition in the business world is getting tighter along with the growth of a region or country. Likewise, business activities in the Clothing industry are also getting tighter and tighter. In the Bandung area, there are clothing industry centers, all of which are MSME artisans. In MSMEs, the weakness that has always been owned is its management and marketing strategy. In this article, what is discussed and done is to improve the business ability of MSMEs by conducting management training and marketing strategies. This activity is also given knowledge on how to make Clothes that conform to national standards. There are 2 forms of management training and marketing strategies that aim to improve the quality of their business. This activity aims to improve the ability of clothing artisans in making quality clothing as one of the marketing strategies